Mitos y tabúes sobre la sexualidad en los estudiantes de Ingeniería Civil de la Universidad Nacional de Chimborazo. - Lema Zambrano, Anthony Xavier (2024)
aimed to determine the myths and taboos about sexuality in civil engineering students at the National University of Chimborazo. Sexuality over the years has generated several myths and taboos in society, which have generated countless fears in both men and women so they cannot express their sexuality in the correct way, which is why many students still maintain some belief in some of these myths and taboos. It is important to stay informed on issues about sexuality, this allows to increase their security and self-love of each person, so that the development of this is cautious and pleasant, without repression in any area. Methodologically, a quantitative approach and non-experimental research design were used. The type of research was basic, field. By the transversal time. By the level of descriptive scope. The sample was non-probabilistic and intentional. For the data collection, a survey (ad hoc) was used with the theme Myths and Taboos about sexuality. The results showed that there are myths and taboos that students are still unaware of and do not socialize for fear of being criticized or judged, additionally this is related to the lack of relevant and truthful information